2019
DOI: 10.1212/wnl.0000000000007562
|View full text |Cite
|
Sign up to set email alerts
|

Axial symptoms predict mortality in patients with Parkinson disease and subthalamic stimulation

Abstract: ObjectiveTo characterize how disease progression is associated with mortality in a large cohort of patients with Parkinson disease (PD) with long-term follow-up after subthalamic nucleus deep brain stimulation (STN-DBS).MethodsMotor and cognitive disabilities were assessed before and 1, 2, 5, and 10 years after STN-DBS in 143 consecutive patients with PD. We measured motor symptoms “off” and “on” levodopa and STN-DBS and recorded causes of death. We used linear mixed models to characterize symptom progression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 44 publications
12
67
0
Order By: Relevance
“…However, a reduction in SNr plasticity was not observed. A recent clinical study [31] demonstrated a 22% worsening in akinetic symptoms and a 27% worsening in axial symptoms over the course of 0 to 2, 5, and 10 years after STN-DBS implantation surgery (with stimulation and medication ON). Assuming a linear progression of these symptoms (which was also demonstrated in the study), these values would deduce to 3.3% (1.32/40) and 4.05% (0.81/20), respectively, over the course of 1.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, a reduction in SNr plasticity was not observed. A recent clinical study [31] demonstrated a 22% worsening in akinetic symptoms and a 27% worsening in axial symptoms over the course of 0 to 2, 5, and 10 years after STN-DBS implantation surgery (with stimulation and medication ON). Assuming a linear progression of these symptoms (which was also demonstrated in the study), these values would deduce to 3.3% (1.32/40) and 4.05% (0.81/20), respectively, over the course of 1.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria for DBS-group were: (1) balance dysfunction caused by secondary Parkinson's syndrome, hydrocephalus, intracranial tumors, and multiple cerebral infarctions. (2) patients with obvious cognitive dysfunction (Montreal Cognitive Assessment<26/30), serious anxiety, depression (Hamilton Anxiety Scale>21/56, Hamilton Depression Scale>24/68); (3) mental illness. All patients provided signed informed consent.…”
Section: Subjectsmentioning
confidence: 99%
“…Falling can have a series of serious consequences, including hip fractures and brain injuries. Due to the fear of falling, the activities of patients with PD are restricted, which seriously affects their quality of life [2]. Until now, improvement of balance function by different treatments remains ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few uncontrolled longterm studies reporting frequencies of key disability milestones in DBS patients and a handful of controlled studies yielding conflicting findings. 3,[10][11][12][13][14][15][16] In this issue of Movement Disorders Clinical Practice, 2 elegant papers addressed whether STN DBS effects wear off and whether DBS patients acquire disability milestones earlier than non-DBS patients. Although driven by different objectives, these studies are complementary and challenged by the unavoidable confounder of evaluating the long-term outcome of a surgical technique adopted in a highly variable and progressive disorder.…”
mentioning
confidence: 99%
“…These results contrast with a recent study suggesting that STN DBS patients with PD survive longer as long as axial symptoms are under control. 15 Despite the use of large cohorts and attempts to match groups properly, any long-term DBS study adopting a historical control cohort of non-DBS patients is heavily biased because of patient selection at baseline. For example, the development of dementia is paradoxically low in DBS cohorts perhaps as a result of strict cognitive screening to determine surgical eligibility.…”
mentioning
confidence: 99%